Biodegradable Polymer-Based Scaffolds for Bone Tissue Engineering - sultana, naznin (SpringerBriefs in Applied Sciences and Technology, 2013)
This book addresses the principles, methods and applications of biodegradable polymer based scaffolds for bone tissue engineering. The general principle of bone tissue engineering is reviewed and the traditional and novel scaffolding materials, their properties and scaffold fabrication techniques are explored. By acting as temporary synthetic extracellular matrices for cell accommodation, proliferation, and differentiation, scaffolds play a pivotal role in tissue engineering. This book does not only provide the comprehensive summary of the current trends in scaffolding design but also presents the new trends and directions for scaffold development for the ever expanding tissue engineering applications.